Need Analysis of Teaching Materials Development for Writing Poetry Based on Contextual Learning (Ctl) Approach in Elementary School - Lilik Fitriani; Fahrurrozi Fahrurrozi; Nidya Chandra Muji Utami (Syntax Corporation Indonesia, 2023)
Learning children's literature appreciation in elementary school is very important so that student's language skills, especially receptive skills, can develop well, one of which is poetry writing skills. Learning to write poetry in elementary schools has not been maximized due to limitations in the provision of teaching materials and approaches used by teachers in improving poetry writing skills. Writing skills are one of the most difficult skills of other language skills, therefore an appropriate approach is needed so that the learning objectives can be realized, one of which is the contextual approach because the contextual approach is the way the teacher conducts the learning process by connecting the real world of students with the subject matter to be learned. The purpose of the study was only to analyze and describe the need of developing teaching materials for writing poetry based on the contextual learning (CTL) approach in elementary schools in Bogor Regency so that the data used was qualitative. Various analyses were conducted to determine the need for developing teaching materials for writing poetry based on a comprehensive contextual learning approach based on conditions, curriculum, and the needs of teachers and students. A comprehensive needs analysis is expected and accurate is expected to be developed for teaching materials for writing poetry based on a contextual learning approach in grade IV elementary schools in Bogor Regency based on the needs of the research field.